PENINGKATAN KOMPETENSI MAHASISWA MELALUI PELATIHAN ENUMERATOR PERIKANAN DI PERAIRAN MEUREBO ACEH BARAT - Eka Lisdayanti; Friyuanita Lubis; Neneng Marlian; Nabil Zurba; Rudi Hermi (LPPM Universitas Islam Darul 'Ulum Lamongan, 2025)
The activity of increasing student competence in fish data collection aims to improve student skills in identifying, collecting and analysing fish diversity in certain waters through training and field practice. This service activity involved 10 lecturers and marine fisheries practitioners, 20 students and 7 local fishermen. Through this activity, students were introduced to basic fisheries survey techniques, the use of environmentally friendly fishing gear, and scientific data processing methods. The programme was implemented through a practical approach in the field by involving fisheries experts, students and local communities. The results of this activity contribute to more accurate mapping of fish resources and improve the quality of research-based learning in the academic environment. In addition, this service activity encourages student awareness of the importance of preserving aquatic ecosystems and the sustainability of fisheries resources.